Moderated Mediating Mechanism Effects of Chinese University Entrepreneurship Education on Independent Student Entrepreneurship - Li, Yuhui; Sha, Yimin; Lv, Yijun; Wu, Yenchun Jim; Liu, Haiming (Frontiers in Psychology, 2022)
Entrepreneurship education plays a mediating moderating role in independent entrepreneurship, especially for the fresh graduates where entrepreneurial knowledge charms. Based on the mediating effect model, this study explores the correlation between three factors and independent entrepreneurship. A set of hypotheses was established by investigating the theoretical background within the field of interest. Such hypotheses were later assessed by an online-offline mix study conducted among graduates. The result found that entrepreneurship theory-based courses can promote independent entrepreneurship, but entrepreneurship practice training surprisingly failed to promote. Entrepreneurial opportunity identification mediated only between theory-based courses and independent entrepreneurship. The findings found could be highly beneficial in organizing entrepreneurship syllabus, scientifically arranging a theory-based course, and practicing a training course. Moreover, it could be further developed into a pedagogical model.